Impact of neutrophil to lymphocyte ratio on survival for hepatocellular carcinoma after curative resection. (3rd October 2017) - Hung, Hao‐Chien; Lee, Jin‐Chiao; Cheng, Chih‐Hsien; Wu, Tsung‐Han; Wang, Yu‐Chao; Lee, Chen‐Fang; Wu, Ting‐Jung; Chou, Hong‐Shiue; Chan, Kun‐Ming; Lee, Wei‐Chen
Abstract: Background: Neutrophil‐lymphocyte ratio (NLR) represents a pro‐tumor inflammatory environment and host immunity. The aim of this study was to examine the effect of subsequent NLR for hepatocellular carcinoma (HCC) after liver resection. Methods: A total of 672 patients had liver resection for HCC were included in this study. NLR at diagnosis of HCC and HCC recurrence were collected. NLR at 2.5 was used as cut‐off value to calculate its prognostic effect. Results: According to NLR cut‐off value, the patients with NLR >2.5 had larger tumor size, higher histology grade, and higher rates of tumor multiplicity and vascular invasion. After a median follow‐up of 76.3 months, 437 (65.0%) patients had tumor recurrence. The 1‐, 3‐ and 5‐year recurrence‐free survival were 77.4%, 55.2% and 44.8% in NLR ≤2.5 group, compared to 64.1%, 45.2% and 35.5% in NLR >2.5 group ( P = 0.016). When patients had tumor recurrence, 5‐year post‐recurrent survival was best in the patients staying with NLR ≤2.5 all the time and decreased from 45.9% to 24.6% if NLR was ≤2.5 at resection and became >2.5 at recurrence ( P = 0.013). Conclusion: High NLR was an independent unfavorable prognostic factor. Subsequent change of NLR between liver resection and HCC recurrence could predict post‐recurrent survival. Abstract : Highlight Hung and colleagues evaluated the prognostic value of the neutrophil‐lymphocyte ratio in patients who underwent liver resection for hepatocellular carcinoma. The neutrophil‐lymphocyte ratio at diagnosis and that at tumor recurrence both had prognostic value. The difference between the initial ratio and that at recurrence could predict survival after new recurrence.